Hubungan Antara Dukungan Keluarga Inti Dengan Prokrastinasi Akademik Mahasiswa. - Saibun Panjaitan; Marisi Simanungkalit; Yohanes Wardoyo; Franky Tuerah; Nathan Roson (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2018)
Core family support is one of the external factors that affect students. Each form of family support has aspects including informative, emotional attention, instrumental assistance and assessment assistance. Students are expected to maintain communication with the nuclear family, in order to continue to get support from the nuclear family. The role of the nuclear family as controls, mentors, regulators and supervisors cannot be immediately erased or eliminated just to be independent or free of expression. In procrastination, it is a student's behavior that is not uncommonly realized but is still being lived out, procrastination makes us think irrationally in a conscious state and looks natural by the surrounding environment. Social support, especially core family support is needed to help the student concerned avoid procrastination. This research was conducted with quantitative research with the technique ofcorrelation analysis product moment. From the results of the analysis shows the direction of the relationship between core family support and academic procrastination, while the value of p <0.01 in Sig. (2-tailed) shows that there is a relationship between core family support and student academic procrastination.